Muscle force characteristics of male and female collegiate cross-country runners during overground running. Issue 5 (3rd March 2020) - Vannatta, C. Nathan; Almonroeder, Thomas G.; Kernozek, Thomas W.; Meardon, Stacey
ABSTRACT: Males and females demonstrate unique running mechanics that may contribute to sex-related differences in common running related injuries. Understanding differences in muscle forces during running may inform intervention approaches, such as gait retraining addressing muscle force distribution. The purpose of this study was to compare muscle force characteristics and inter-trial variability between males and females during running. Twenty female and 14 male collegiate cross-country runners were examined. Three-dimensional kinetic and kinematic data were collected during overground running and used to estimate muscle forces via musculoskeletal modelling. Principle components analysis was used to capture the primary sources of variance from the muscle force waveforms. The magnitude of the forces for the hamstrings, gastrocnemius, and soleus muscles were higher across the majority of stance in male runners regardless of footstrike pattern. Males also demonstrated greater inter-trial variability in the timing of the peak gluteus maximus force and the magnitude of local peaks in the gastrocnemius force waveform. Male and female collegiate cross-country runners appear to employ unique lower extremity muscle force characteristics during overground running.